2000
DOI: 10.1038/modpathol.3880164
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Arising in Recurrent Respiratory Papillomatosis with Pulmonary Involvement: Emerging Common Pattern of Clinical Features and Human Papillomavirus Serotype Association

Abstract: Squamous papillomas of the lung are an uncommon feature of recurrent respiratory papillomatosis, occurring in fewer than 1% of cases. We describe a 23-year-old patient with pulmonary papillomas who developed a fatal squamous cell carcinoma of the lung. PCR-based human papillomavirus (HPV) typing showed the presence of HPV 11 DNA in both benign papillomas and invasive carcinoma. A review of the literature reveals four reports of malignant transformation of juvenile-onset recurrent respiratory papillomatosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 18 publications
(23 reference statements)
6
53
0
3
Order By: Relevance
“…The finding that punctate ISH signals are common in both juvenile-onset (7/10) and adult-onset (7/11) patients infected with low-risk HPV genotypes, suggests that HPV integration into the cell genome occurs at an early stage and may be an important factor contributing to the recurrent nature of these lesions. Possibly, if HPV integration occurs in a basal stem cell, HPV is then locked into the cell genome at the site of laryngeal infection and thereafter may support the recurrent papilloma phenotype and eventually the conversion of laryngeal papillomas to carcinomas, especially in juveniles [6,7]. In cervical tumors, high-risk HPV integration is associated with the loss of the HPV E2 gene that regulates the E6 and E7 oncogenes that promote abrogation of cell cycle control and cell division; low-risk HPV integration may support a parallel situation in recurrent papillomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that punctate ISH signals are common in both juvenile-onset (7/10) and adult-onset (7/11) patients infected with low-risk HPV genotypes, suggests that HPV integration into the cell genome occurs at an early stage and may be an important factor contributing to the recurrent nature of these lesions. Possibly, if HPV integration occurs in a basal stem cell, HPV is then locked into the cell genome at the site of laryngeal infection and thereafter may support the recurrent papilloma phenotype and eventually the conversion of laryngeal papillomas to carcinomas, especially in juveniles [6,7]. In cervical tumors, high-risk HPV integration is associated with the loss of the HPV E2 gene that regulates the E6 and E7 oncogenes that promote abrogation of cell cycle control and cell division; low-risk HPV integration may support a parallel situation in recurrent papillomas.…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile-onset RRP (JO-RRP) is generally considered to have a more aggressive clinical course than the adultonset (AO-RRP) [2,4,5]. Also, conversion to laryngeal carcinoma occurs more frequently in juveniles [6,7]. In addition to having a different clinical course, JO-RRP differs in its route of acquisition; while numerous studies have indicated that vertical transmission from maternal genital condylomas is the primary mode of juvenile papillomas, adult papillomas apparently spread secondary to oral-genital contact [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports suggested HPV 11 is associated with a transformation to squamous cell carcinoma. 2,3,8) Our patient was female and relatively older than most patients with adult onset papillomas. The route of HPV transmission was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In juvenile onset RRP, HPV is thought to be acquired at the time of vaginal delivery. 3) In one case control study, 9) adult onset RRP patients had more sexual partners and oral sex than their controls. HPVs cause latent airway infection, in addition to the active infection, that induces papillomas, and activation of latent HPV DNA, which appears to persist for the life of the patient, is considered to be the cause of recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation